A remodelled approach to measuring the social impact of tourism in a developing country. Issue 6 (2nd November 2018) - Scholtz, Marco; Slabbert, Elmarie
ABSTRACT: Residents living in communities with tourism activities form a vital part of the tourism industry; without their support, the industry will likely fail. It is the understanding of the Social Exchange Theory that residents should receive a form of physical award for accepting visitors into their environment, however, with the case of South Africa, there are various factors that inhibit the flow of such benefits. Regardless, the residents remain supportive. It was therefore determined that the intangible social impacts of tourism also play a vital role in fostering community support. To better manage both the tangible and intangible social impact perceptions, a framework was successfully developed by means of structural equation modelling (SEM). This novel framework may aid tourism managers to predict and strategically manage the social impact perceptions of tourism in a developing country such as South Africa in order to foster the vital community support for this industry. Abbreviations: SEM: Structural equation modelling